Обґрунтування ролі звітності в управлінні промисловим підприємством на засадах ощадливості - Колос, Ірина Василівна (My University, 2016)
У статті встановлено зміну орієнтирів ощадливого мислення в управлінні промисловим підприємством від ефективності і продуктивності через цінність для клієнта до якості і сталого розвитку. Обґрунтовано в історичному аспекті звітність з урахуванням зміни акцентів ощадливості. Враховуючи унікальність промислового підприємства, доведено доцільність формування інтегрованого звіту про підвищення ефективності ощадливих перетворень. The article discusses the importance of reporting as a source of relevant and accurate information in the management of industrial enterprise in the context of lean changes on an ongoing basis. Retargeting of lean thinking in the management of industrial enterprise from efficiency and productivity across the value for the customer to quality and sustainable development is established based on the analysis and synthesis of scientific development. Reporting of the enterprise is grounded in historical aspect with accounting experience of its formation according to the change of lean emphasis. Given the uniqueness of the industrial enterprises, the expediency of forming an integrated report using operating performance ratio on lean principles is proved.
Keywords: кафедра обліку і аудиту; фінансова звітність; звітність підприємства; ощадливе виробництво; lean виробництво